Tattoo and Body Piercings among Young Adults in Nigeria - Abimbola, Ebeye Oladunni; Itohan, Osahon Roli; Ehizokhale, Ehebha Santos; Chuwuma, Ojumah Nancy; Godswill, Okoro Ogheneyebrorue; Enatewe, Akpoyibo Emmanuel (International Journal of Human and Health Sciences (IJHHS), 2022)
Objective: Both tattoo and body piercing have a long history and are well known in various cultures in African, American, Asia, and Oceania. Although the appearance of the two varies geographically, they always possess a specific meaning for a particular culture. This study examined awareness, attitude, and knowledge of students towards tattooing and body piercing in Delta State University, Abraka. Nigeria. Material and Methods: Data was collected through the use of well-structured questionnaires. The study made use of 400 young adults randomly selected from six faculties in Delta State University, Abraka. Result and Discussion: Findings revealed that the majority of students (85%) are aware of tattoo and body piercing and 31.3% gave fashion as the main reason why they engage in body modifications. It was however observed that 40% of the subjects under survey regard their colleagues involved in tattooing and body piercing as irresponsible and reckless. Conclusion: The study gave a growing convergence on both gender toward tattooing and a sharp difference in the involvement of both gender towards body piercing. Majority of these young adult are also aware of the health risks associated with body modifications and may not consider them in future. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 24-29